E-name card application - Koh, Alvin Jun Ming (Nanyang Technological University, 2022)
As a marketing tool, name cards are extremely important in the corporate world. These name cards can help introduce our firms or personal profiles by providing information such as our names, phone numbers, and email addresses. The majority of people have long used the method of exchanging physical name cards when they meet. Physical meetings have been supplanted by virtual meetings due to the quick speed of digital change and the rising reliance on technology for social contact over the previous decade. Furthermore, as a result of the COVID-19 epidemic, there is a growing demand for digitalization, and traditional name cards are becoming increasingly obsolete. As the demand for contactless technology grows, many working professionals are opting for digital name cards instead. As a result, as part of the new digital readiness and business continuity planning for the post-pandemic new normal, a digital substitute to the traditional paper version is urgently needed. To push name card digitization even further, a free-to-use application platform that allows users to make customised name cards with minimal effort must be conceptualized and developed. This project will be coded in Visual Studio Code and will use Node.js, one of the most popular web application programming languages. It will also be hosted on Amazon Web Services, the world's most popular public cloud platform.